Psych-education major students' profile - Maria Regina Peres (Universidade Federal de Santa Maria, 2014)
Among our post-graduate courses, Psych-Education demand has grown in the last few years. Little is known about the professionals who seek these courses. A research was done on a group of 251 new students in the Psych-Education Graduate course from 2005 to 2012, with the expectation of understanding the students profile and objectives. A questionnaire was provided to discover their major area of study in their Bachelor's degree, work experience, and future aspirations. The results indicated that most students were Education majors who work now in the teaching profession with the objective of obtaining more professional training. It was concluded that these professionals are seeking alternative methods of teaching that will enhance the educational field.